A MODEL OF PETROLEUM PIPELINE SPILLAGE DETECTION SYSTEM FOR USE IN THE NIGER DELTA REGION OF NIGERIA - OvueleloloOkorodudu, Franklin; OgheneogagaOkorodudu, Philip; Kennedy Irikefe, Ekerikevwe (International Journal of Research -GRANTHAALAYAH, 2016)
In recent times, petroleum pipeline vandalism resulting into spillage has become a significant challenge in Nigeria. Citizens are regularly inundated with reported cases of vandalism which often lead to spillage and a drastic reduction in government’s revenue as is currently the case in Nigeria. This paper focuses on the design of petroleum pipeline spillage detection system. The design consists of the power supply unit, the comparator unit, the microcontroller unit, the switching unit, the transceiver unit and the base station. Simulation of the various units was done individually using the procedural programming application Proteus 8. Most of the components used were according to design specifications from data book with alternatives used in cases where they are unavailable. Wiring sensors which provided continuous electrical paths to break the signal path and trigger an alarm at the base station were used The design was done in units and were tested individually and the whole system was tested to perform the required task of detecting petroleum spillage and alerting the control room for action. It is found that the designed system had the advantage of responding to intrusion and vandalism better than existing systems.